A colorimetric and ratiometric fluorescent probe with ultralow detection limit and high selectivity for phosgene sensing. (April 2019) - Liu, Peilian; Liu, Na; Liu, Cuiling; Jia, Yongmei; Huang, Liping; Zhou, Guohua; Li, Chengpeng; Wang, Sheng
Abstract: Phosgene is a kind of colourless and extreme toxic gas that poses a serious threat to public health and safety. A colorimetric and ratiometric fluorescent probe (AC-6ED ), with anthracene carboximide as fluorophore and ethylenediamine group as recognition moiety has been developed for phosgene detection in solutions and in the gas phase based on the intramolecular charge transfer (ICT) mechanism. TheAC-6ED traps phosgene molecule via intramolecular cyclization reaction to afford color and fluorescence emission change. TheAC-6ED features low detection limit (0.09 nM), fast response (<20 s), remarkable colorimetric and ratiometric signal, excellent selectivity for phosgene over other interference analytes such as nerve agent mimics, various acyl chlorides and analogues. TheAC-6ED loaded TLC plate can serve as a highly selective tool for phosgene sensing in the gas phase below health risk concentrations in a fast, portable, visible, and highly sensitive manner. Graphical abstract: Highlights: A new colorimetric and ratiometric fluorescent probe has been designed and synthesized. The probeAC-6ED shows ultralow detection limit and high selectivity for phosgene sensing. TheAC-6ED loaded TLC plate can serve as a portable tool for phosgene sensing in the gas phase.